Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1111/jfpp.16294
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of fenugreek seed oil and oil load effect on maltodextrin and fenugreek seed mucilage as wall materials by spray drying

Abstract: This work aims to encapsulate the fenugreek seed oil (FGSO) to musk the bitter taste as it has various health benefits using maltodextrin and fenugreek mucilage as the wall materials by spray drying. The highest powder yield was 68.23% at 1.5% oil, 2% mucilage, and 10% maltodextrin. The powder moisture content ranged from 4.5 to 6.8%. The bulk density, tapped density, Carr's index and Hausner's ratio was evaluated and the powder showed good flowability. All the peaks obtained by FTIR of powder were similar, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 57 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…The higher HR values indicate more cohesive powders that are less able to flow freely (Alpizar‐Reyes et al ., 2020). The HR values of all samples were above 1.35, indicating poor flowability (Munshi & Kumar, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher HR values indicate more cohesive powders that are less able to flow freely (Alpizar‐Reyes et al ., 2020). The HR values of all samples were above 1.35, indicating poor flowability (Munshi & Kumar, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The 7.5 min mucilage had the lowest tapped and bulk density results. Munshi & Kumar (2022) reported that the bulk and tapped densities of fenugreek seed mucilage were 510 and 590 kg m À3 , respectively. The bulk and tapped densities of okra mucilage as reported by Okunlola (2021) were 508 and 594 kg m À3 , respectively.…”
Section: Bulk and Tapped Densitymentioning
confidence: 99%
“…Moreover, encapsulation prolongs the shelf life of FGSO and stops bioactive components from degrading (Munshi & Kumar, 2022).…”
Section: Fenugreek Seed Oil Encapsulationmentioning
confidence: 99%
“…To mask the bitter flavor of the oil and make it edible, FGSO can be encapsulated with maltodextrin and fenugreek. Moreover, encapsulation prolongs the shelf life of FGSO and stops bioactive components from degrading (Munshi & Kumar, 2022 ).…”
Section: Applications Of Fenugreek Seeds In Nanotechnologymentioning
confidence: 99%